Advantages and Limitations of Online Dictionaries (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article presents a comprehensive analysis of the advantages and limitations of online dictionaries of the English language as a distinct type of digital lexicographic resource. The study is conducted within the framework of functional, cognitive, and digital lexicography and is grounded in contemporary approaches to linguistic variation and the discourse-conditioned nature of meaning. The empirical basis of the research consists of data drawn from leading English-language online dictionaries, including Oxford English Dictionary Online, Merriam-Webster Online, and Cambridge Dictionary. Particular attention is paid to the dynamics of the lexicon, multimodality of data representation, corpus-based verification, as well as issues of normativity, methodological heterogeneity, and cognitive reduction in lexicographic description.